From Picky Eaters to Nourished Explorers: Unveiling the Power of Responsive Feeding in Enhancing Young Children’s Nutrition - Winahyu, Karina Megasari; Perdani, Zulia Putri; Kartini, Kartini; Astuti, Astuti (Faletehan Health Journal, 2023)
Implementing responsive feeding is essential for modifying the nutritional status and overall well-being of young children. The aim of this narrative review is to provide a thorough synthesis of the current evidence on responsive feeding and its impact on the nutritional status of young children. Searches were conducted in PubMed and Medline with keywords "Responsive feeding," AND “young children”. The inclusion and exclusion criteria were defined to choose the most pertinent studies. The initial search yielded 106 articles, with a total of 22 full-text articles examined, 12 of which were appropriate for inclusion. The review emphasizes the function of responsive feeding in maintaining healthy eating habits, reducing childhood obesity, and promoting optimal growth and development in young children. The study highlights the significance of early nutrition treatments that prioritize responsive feeding to enhance nutritional quality and foster healthy eating habits during early childhood. It also discusses the difficulties that caregivers experience when implementing responsive feeding methods, such as competing societal norms and external influences. Furthermore, the review identifies data gaps and recommends additional studies to investigate the long-term impacts of responsive feeding on children's nutrition, and health outcomes. In conclusion, the narrative review underlines the significance of responsive feeding in supporting optimal nutrition and healthy eating habits in young children.